Firm Performance and Trade with Low-Income Countries: Evidence from China - Hans-Jörg Schmerer; Luhang Wang (Center for Economic Studies and ifo Institute (CESifo), 2014)
Do firms in developing countries shift trade towards developed economies as a result of high economic growth? The matched customs-manufacturing firm data used in this study confront this hypothesized link with empirical evidence. Our analysis reveals a rising low-income country trade share around and after China's accession to the World Trade Organization. Based on this stylized fact, we analyze the link between firm characteristics and trade with low-income countries. We find evidence for sequential sorting into different export-modes according to firm productivity: i) only the most productive firms export to low-income countries, ii) exporting to low-income countries is mostly coupled to exporting to high-income countries, and iii) firms that switch to export to markets with higher potential are younger than firms that switch to export to both high- and low-income markets. Moreover, we find that firms tend to start exporting through specialization on high-income markets before diversifying to both type of markets.
Keywords: F10; F60; O10; 330; trade with low-income countries; productivity; Chinese firms; firm level data; finance constraints; sequential exporting